KUALITAS PENDIDIKAN DI INDONESIA - Mondy Larasati (Bajang Institute, 2022)
Education is a basis or foundation for obtaining a good life. The quality of education is the ability of educational institutions to utilize educational resources to improve learning abilities as optimally as possible. The purpose of writing this article is to find out the quality of education in Indonesia, the problems that cause the low quality of education in Indonesia, as well as solutions to improve the quality of education in Indonesia. Because the quality of education is one of the determinants of the progress of a country. This article describes the problems that cause the low quality of education in Indonesia, and also solutions that can be taken to improve the quality of education in Indonesia. With this article, I hope that the awareness of each individual will arise to create a better quality of education in Indonesia.